Risiko dan kinerja Bank Perkreditan Rakyat: Studi perbandingan antara BPR Syariah dengan Konvensional di Indonesia - Sutrisno Sutrisno (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2017)
The aims of this study were to examine the effect of risks consisting of credit risk (NPL/NPF), capital risk (CAR), liquidity risk (LDR/FDR), and operating risk (OEOI) on rural banking performance as measured by return on assets ROA), the differences in risk and performance of Islamic Rural Banking (IRB) and Conventions Rural Banking (CRB). The population is all banking in Indonesia whether operating in Islamic or conventionally with purposive sampling method. The results showed that NPL in CRB had not significant effect, while NPF IRB had negative significant effect on performance. In contrast, CAR on Islamic Rural Banks had not significant effect, while CAR of conventional rural banking has positive significant effect on performance. Liquidity risks (LDR/FDR), both IRB and CRB have positive significant impact on performance. While the operational risk (OEOI) has a negative significant effect on the performance of CRB as well as IRB. Differential test results indicate that there are significant differences between CRB and IRB in terms of profitability (ROA), credit risk (NPL / NPF), liquidity risk (LDR / FDR) risk, and operating risk (BOPO).